Soft Clay Engineering and Ground Improvement - Ameratunga, Jay; Sivakugan, N. (Nagaratnam), 1956-; Das, Braja M., 1941- (Abingdon, Oxon ; Boca Raton, FL: CRC Press, 2021)
Soft Clay Engineering and Ground Improvement covers the design and implementation of ground improvement techniques as applicable to soft clays. This particular subject poses major geotechnical challenges in civil engineering. Not only civil engineers, but planners, architects, consultants and contractors are now aware what soft soils are and the risks associated with development of such areas. The book is designed as a reference and useful tool for those in the industry, both to consultants and contractors. It also benefits researchers and academics working on ground improvement of soft soils, and serves as an excellent overview for postgraduates. University lecturers are beginning to incorporate more ground improvement topics into their curricula, and this text would be ideal for short courses for practicing engineers. It includes several examples to assist a newcomer to carry out preliminary designs. The three authors, each with dozens of years of experience, have witnessed and participated in the rapid evolvement of ground improvement in soft soils. In addition, top-tier professionals who deal with soft clays and ground improvement on a daily basis have contributed, providing their expertise in dealing with real-world problems and practical solutions.
OCLC-licensed vendor bibliographic record.
Keywords: Engineering geology; TECHNOLOGY / Engineering / Civil